“I really think that you should speak out”: vocational students’ reactions to sexual harassment from patients and care recipients - Maria Hedlin; Eva Klope (Empirical Research in Vocational Education and Training)
Abstract Vocational education can have a significant role and important function in preparing students for work in professional fields where sexual harassment is common. Assistant nurses constitute a group that is at great risk of being subjected to sexual harassment by patients. Yet little is known about how vocational students training for the job react to the violations. The research question guiding this study is: How do students undergoing training for the assistant nurse vocation describe their reactions to being subjected to sexual harassment from patients and care recipients? The empirical material consists of focus group interviews with vocational students undergoing assistant nurse training in Swedish upper secondary school. The students who took part in the focus groups were in their third and final educational year. The groups comprised a total of 42 students, 32 women and 10 men. The students described three types of reaction; (1) experiencing discomfort and powerlessness, (2) trying to distract or interrupt and (3) speaking out. Speaking out is the reaction that may be considered the most appropriate, while at the same time being the one that is the most difficult to reconcile with prevailing femininity norms, implying that such a strategy can be perceived as impossible for those young women at risk of being subjected to sexual harassment.